2013
DOI: 10.1016/j.joca.2012.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Chondrogenic potentials of human synovium-derived cells sorted by specific surface markers

Abstract: Our study suggests that CD105 and CD166 would be valuable surface markers associated with chondrogenic potential; thus, CD105- and CD166-enriched cells derived from human synovium would be practical and valuable sources for cartilage regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 33 publications
2
20
0
1
Order By: Relevance
“…The ADSCs of murine origin expressed CD105 but its expression varied with passage number and cell density. When ADSCs were CD105 negative, they were more inclined to differentiate into osteocytes and adipocytes [Anderson et al, 2013], whereas the presence of CD105 favored chondrogenic transformation [Chang et al, 2013]. In our study, the decrease in CD105 mRNA abundance in the absence of FBS (TRT2 and TRT4) is, therefore, indicative that the absence of FBS promotes lineage differentiation towards adipocytes irrespective of the fact that CD105 was still expressed at a low level in each TRT.…”
Section: Discussionmentioning
confidence: 45%
“…The ADSCs of murine origin expressed CD105 but its expression varied with passage number and cell density. When ADSCs were CD105 negative, they were more inclined to differentiate into osteocytes and adipocytes [Anderson et al, 2013], whereas the presence of CD105 favored chondrogenic transformation [Chang et al, 2013]. In our study, the decrease in CD105 mRNA abundance in the absence of FBS (TRT2 and TRT4) is, therefore, indicative that the absence of FBS promotes lineage differentiation towards adipocytes irrespective of the fact that CD105 was still expressed at a low level in each TRT.…”
Section: Discussionmentioning
confidence: 45%
“…Accordingly, CD73 is highly expressed on synovial stromal cells (10). A second possibility is that CD73 expression on endothelial cells regulates joint inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…CD73 on nonhematopoietic cells plays an important role in the control of CIA CD73 is expressed on both hematopoietic and nonhematopoietic cells (10). Notably, CD73 is expressed at high levels on human joint synovial cells (Supplemental Fig.…”
Section: Cd73-deficient Mice Are More Susceptible To Ciamentioning
confidence: 99%
“…It is documented that MSCs directly act in cartilage formation, as well as release trophic factors, and promote angiogenesis [9–11]. Amongst the various available sources, MSCs seem to have many advantages over their counterparts, while recent study demonstrated that synovium-derived MSCs (SMSCs), which have better chondrogenic potential compared with MSC, are gaining momentum [1217]. Improved MRI features, histology, and better clinical outcome have been achieved in cartilage repair derived from SMSCs [14].…”
Section: Introductionmentioning
confidence: 99%